Ocean Circulation and Climate : a 21st Century Perspective - Siedler, Gerold; Griffies, Stephen M., 1962-; Gould, W. John (William John), 1942-; Church, John, 1951- (International geophysics series ;, 2013)
This book provides a summary of the state of the science relating to the role of the oceans in the physical climate system. It is structured to guide the reader through the analysis, interpretation, modeling, and synthesis of ocean climate phenomena.